(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
A comparison is made between the pricing strategies of popular cloud platforms, including Google Cloud Platform, Microsoft Azure, and Amazon Web Services. The research paper looks at the structure, cost-effectiveness, flexibility, and applicability of several pricing schemes, such as pay-as-you-go, reserved instances, and spot pricing. By highlighting the advantages and disadvantages of each model, the research seeks to offer recommendations for strategic planning and ideal cloud cost management through case studies and analytical comparison. Highlighting important cloud computing and associated service companies, such as AWS, Microsoft Azure, and GCP. It outlines study objectives to find and suggest the most effective pricing methods for companies and describes how comparing cloud pricing models can be difficult. According to the results, choosing the appropriate price plan and cloud platform is crucial for cost savings and scalability without sacrificing performance or dependability.